Respostas

A melhor resposta!
2014-04-30T00:31:41-03:00
f(x) = ax+b
============================

f(-1) = a.3+b
f(-1) = 3

3a + b = 3

============================
f(1) = a1+b
f(1) = 1
a + b = 1

============================
a + b = 1
b = 1 - a
---------------------------------------------------------
3a + b = 3
3a + 1 - a = 3
2a = 3 - 1
2a = 2
a = 2/2
a = 1
---------------------------------------------------------
a + b = 1
1 + b = 1
b = 1 - 1
b = 0

=============================
f(x) = ax+b
f(3) = 1.3+0
f(3) = 3





1 5 1